Development of hybrid aluminum/carbon fiber/pineapple leaf fiber laminates using vacuum assisted resin transfer molding (VARTM) for automotive applications - Xiao, Hanyue; Hameed Sultan, Mohamed Thariq; Shahar, Farah Syazwani; Nayak, Suhas Yeshwant; Yidris, Noorfaizal; Md Shah, Ain Umaira (Springer Nature, 2023)
The hybridization of natural and synthetic fibers is an alternate method to balance the performance and environmental friendliness of fiber metal laminates (FMLs). This research aims to fabricate hybrid aluminum (A)/ carbon fiber (C)/ pineapple leaf fiber (P) reinforced epoxy FMLs with different stacking sequences by the vacuum-assisted resin transfer molding (VARTM) technique. The fabricated hybrid FMLs were subjected to tensile, flexural, thermogravimetric analysis (TGA), and water absorption tests. The tensile and flexural strength of hybrid A1 (ACPCA) surpassed those of non-hybrid AP (APPPA) by 252.77% and 165.08%, respectively. The thermal test shows that the hybrid FMLs A1 with higher CF content leads to better thermal stability than A2 (APCPA). In addition, from the water absorption test, the AP and A2 FMLs, with PALF as outer layers of core materials, absorbed moisture exceeding 6% after 10 weeks, compared to AC (ACCCA) and A1 with CF as outer layers of core materials, which only reached up to 2.88% and 4.22%, respectively. From this study, it is worth pointing out that the hybrid A1 showed comparable performance to non-hybrid AC. Thus, the appropriate hybridization of synthetic and natural fibers can broaden the scope of the practical application of FMLs with improved environmental friendliness in the automotive industry.